STRATEGI DAN TANTANGAN WOMEN LEADERSHIP DALAM PERJUANGAN SOSIAL YANG BERKELANJUTAN - Emmywati; Endang Setyawati; Ketut Witara (ITB AAS Indonesia Surakarta, 2026)
This study aims to analyse the strategies and challenges of women's leadership in sustainable social struggles at the local community level. The focus of the study is on the Family Empowerment and Welfare (PKK) organisation of RT 01, RW 04, Medokan Ayu Village, Surabaya, which is a concrete example of community-based women's leadership in driving social participation and community empowerment. This study uses a qualitative approach with descriptive phenomenology to understand the meanings and life experiences of women leaders. Data was obtained through in-depth interviews with six key informants, participatory observation in community activities, and documentation studies. Data analysis was conducted using the Colaizzi method to identify the main themes from the participants' experiences. The results of the study reveal three main themes, namely: empathy-based leadership and family values, adaptive strategies for dealing with socio-cultural obstacles, and commitment to the sustainability of social struggle through collective participation. These findings show that women leaders in the PKK community are able to integrate local social and cultural values into their leadership practices. The novelty of this research lies in the emergence of the Local Wisdom Leadership conceptual model, a form of women's leadership rooted in empathy, collaboration, and local cultural values, which can serve as the basis for the development of inclusive and sustainable women's empowerment programmes.